Monetary Policy, Investment Dynamics, and the Intertemporal Approach to the Current Account - Michael Magill; Kristin Van Gaasback; Paul Bergin (University of California, Department of Economics, 1997)
This paper applies the intertemporal approach to the current account to the case of monetary shocks. A two-country dynamic general equilibrium model with predetermined wages is proposed as a means to bridge the gap between Mundell-Fleming and modern intertemporal models. Early versions of Mundell-Fleming implied that a monetary expansion must necessarily improve the current account; the alternative result became a possibility in more contemporary versions when intertemporal features were introduced into the asset market. The present model suggests that when intertemporal features are also introduced into the other markets of the economy, the model''s prediction is transformed yet further. A calibrated version of the model suggests a beggar-thy-neighbor improvement in the current account becomes unlikely for reasonable parameter values.
Keywords: 330